The role of aberrant salience and alexithymia in psychotic experiences of non-treatment-seeking adolescent immigrants compared with natives - Pozza A (Dove Medical Press, 2019)
Andrea PozzaDepartment of Health Sciences, University of Florence, 50135 Florence, ItalyIntroduction and objectives: Immigration in Europe is a challenge for health care systems. Psychotic experiences are not uncommon in the community. Meta-analyses showed that immigrants are at higher risk of psychotic symptoms and experiences than natives. In the international literature, there is little knowledge about the psychological processes explaining the relationship between immigrant status and psychotic experiences. Aberrant salience, the biased assignment of significance to otherwise innocuous stimuli, and alexithymia (difficulty identifying/verbalizing feelings and concrete speech/thinking) have been found to be vulnerability/maintenance factors of psychotic symptoms. This report presents a study investigating whether: 1) adolescent immigrants in Italy report more intense psychotic experiences than natives; 2) aberrant salience and alexithymia predict more intense psychotic experiences; and 3) these psychological processes moderate the effect of immigrant status on psychotic experiences. Knowledge about the role of these processes in psychotic experiences may suggest early detection or prevention strategies.Methods: One hundred and forty-eight community adolescents were recruited (mean age =17.57 years, 47.30% females); of these, 75 were born in Italy (natives) and 73 were immigrants (born in countries other than Italy). The Aberrant Salience Inventory, the Toronto Alexithymia Scale-20, and the Screening for Psychotic Experiences were administered in classrooms.Results: Immigrants had higher aberrant salience (F=4.38, p<0.05), alexithymia (F=8.93, p<0.01), and psychotic experiences (F=10.65, p<0.01) than natives. Higher aberrant salience and alexithymia predicted more intense psychotic experiences. An interaction effect between immigrant status and alexithymia emerged: immigrants with higher alexithymia had more intense psychotic experiences (β=0.17, p<0.001).Conclusion: Early detection or prevention programs should focus on aberrant salience in the adolescent population and should consider young immigrants with higher alexithymia as a subgroup with higher psychotic experiences. Mindfulness-based programs may be implemented for this adolescent subgroup to promote emotional intelligence.Keywords: aberrant salience, emotional awareness, psychotic experience, adolescents, immigrants, emotional intelligence